Mitochondrial DNA Evaluation and Species Identification of Kemp’s Ridley Sea Turtle (Lepidochelys kempii) Bones After a 3-Year Exposure to Submerged Marine and Terrestrial Environments - Krestoff, Elizabeth S.; Creecy, James P.; Lord, Wayne D.; Haynie, Michelle L.; Coyer, James A.; Sampson, Kate (Frontiers in Marine Science, 2021)
Because Kemp’s ridley sea turtles (Lepidochelys kempii) are critically endangered and closely related to the vulnerable olive ridleys (L. olivacea), it is essential for forensic investigations and conservation efforts to distinguish these species when only skeletal elements remain. DNA extraction and analysis by DNA sequencing of genetic markers is the only method to determine species identity reliably, yet these methods are significantly compromised when DNA becomes degraded. To evaluate the role that time and environment play in obtaining high-quality DNA sequencing data, we placed skeletal elements of a terrestrial mammal (Bos taurus) and L. kempii in a supratidal and subtidal environment for 3 years. Bi-annual sampling revealed that after 3 years, mitochondrial DNA (mtDNA) consistently identified each species from each environment. Our results show that mtDNA recovery from bone and identification for Kemp’s ridley sea turtles was possible up to 3 years in both environments. All sequencing data obtained was accurate and robust, but DNA sequencing results were not consistent after 664-days of exposure. Our findings led us to conclude that if sufficient DNA is extracted from bone samples, then high-quality sequence data can be obtained, and the resulting sequence data accurately reflects the reference sequence for the given gene marker. This study provides evidence that DNA can be extracted and analyzed from challenging biological substrates, like bone, when these substrates are exposed to seasonally dynamic maritime environmental conditions for up to 3-years.